Contemporary comprehension of root canal biofilms and future perspectives: Part 1 - Vijetha Vishwanath; Prasanna Neelakantan (Wolters Kluwer Medknow Publications, 2024)
Apical periodontitis is an inflammatory response of the periradicular tissues to microbial infection of the root canal system (intraradicular infection) or to biofilms attached to the external surface of the root (extraradicular infection). Over the past few decades, our understanding of how microbiota initiate, progress, and sustain disease has been well characterized. In parallel, state-of-the-art approaches have attempted to demonstrate the spatiotemporal complexity of biofilm communities both within the tooth and elsewhere in the body. Despite all this research, translation of such critical knowledge into biofilm management in endodontics has been minimal, in part because of lack of directional clarity. The purpose of this commissioned review is to highlight our current understanding of root canal microbial communities as a cause of pulpal and periradicular disease. While several reviews have been written on this topic, few have delved deep into the biogeography, assembly, and functional profile, a void which this review will attempt to fill. The authors hope that this review will open out-of-the-box thinking and newer perspectives in biofilm management in endodontic treatments.